2019
DOI: 10.1007/s10212-019-00452-6
|View full text |Cite
|
Sign up to set email alerts
|

Can social and emotional learning improve children’s academic progress? Findings from a randomised controlled trial of the Promoting Alternative Thinking Strategies (PATHS) curriculum

Abstract: Despite the significant evidence base demonstrating the positive impact of the Promoting Alternative Thinking Strategies (PATHS) curriculum on children's social-emotional and mental health outcomes, there has been very little research on its efficacy in improving academic attainment. More generally, the relationship between implementation variability and PATHS intervention outcomes has been underexplored. A cluster-randomised controlled trial with two arms: intervention (PATHS-23 schools) and control (usual pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(73 reference statements)
1
7
0
Order By: Relevance
“…In contrast, other implementation features, such as quality, were difficult to extract due to limited information in most experimental studies. This distinguishing feature of dosage was partially supported by Hennessey and Humphrey (2020), who explained that distinct implementation profiles mainly differed in the levels of dosage irrespective of fidelity, quality, responsiveness and reach. Therefore, dosage is an excellent distinguishing feature of implementation, and its moderation effect on the outcomes of PATHS is supported in the current review.…”
Section: Conclusion and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, other implementation features, such as quality, were difficult to extract due to limited information in most experimental studies. This distinguishing feature of dosage was partially supported by Hennessey and Humphrey (2020), who explained that distinct implementation profiles mainly differed in the levels of dosage irrespective of fidelity, quality, responsiveness and reach. Therefore, dosage is an excellent distinguishing feature of implementation, and its moderation effect on the outcomes of PATHS is supported in the current review.…”
Section: Conclusion and Discussionmentioning
confidence: 88%
“…Social emotional learning is often considered to be supplementary in schools (e.g., Murray et al, 2014;Gaspar et al, 2018;Seabra-Santos et al, 2018). Even if some schools do conduct curriculum-based social emotional learning programs, it is difficult to guarantee the dosage of courses (Bierman et al, 2008;Hamre et al, 2012;Berry et al, 2016;Humphrey et al, 2016;Hennessey and Humphrey, 2020). However, social emotional skills are at least as important as cognitive skills in predicting personal achievement in the future (Heckman et al, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As Durlak (2016) noted, though, implementation components can interact with one another, and despite evidence suggesting better implementation is associated with more promising program outcomes, there is a lack of systematic investigation of how patterns of implementation factors relate to different program outcomes. While traditional variable-centered analyses (e.g., Analysis of Variance, correlation, and regression) have been widely used in many implementation studies, these methods may be insufficient for examining inter-relationships among multiple implementation measures (Laursen and Hoff, 2006;Hennessey and Humphrey, 2020). Furthermore, variable-centered approaches assume that the population is homogeneous in terms of how predictors impact outcomes (Laursen and Hoff, 2006;Cheng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging the multi-faceted and multiplicative nature of implementation, the likely dynamic interplay between implementation aspects, and the lack of clarity about what matters most for schoolbased SEL, recent studies have identified person-centered profiles of implementation using multiple indicators and investigated their association with student outcomes. We located two studies that Hennessey and Humphrey (2020) also identified four profiles of implementation for PATHS (Greenberg and Kusche, 1993) based on adherence, quality, dosage, reach, and engagement. The analysis sample was composed of 45 schools that implemented the program for children 9-11 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation